Features of digital broadcasting in Kazakhstan (Herald of Journalism, 2020)
The article investigates the key points of the development of digital terrestrial television in Kazakhstan, especially television broadcasting in the context of new digital technologies.
Keywords: digital television, GE-06, TV signal, satellite broadcasting, digital terrestrial TV.